Iceland : 2018 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Iceland. (IMF Staff Country Reports; Country Report ;, 2018)
Iceland is experiencing an economic slowdown that has reduced overheating concerns. Tourism growth has decelerated and the krona has stopped appreciating. Demand management has become easier, allowing the authorities to focus on medium-term priorities, including infrastructure, healthcare, education, and the environment. Risks, however, have become more evident. High fuel prices and other factors are challenging the airline business; world trade tensions are escalating; and the United Kingdom-a vital trading partner-is not yet assured of a smooth EU exit. Icelandic policies thus need to focus on further increasing resilience to shocks.